MENINGKATKAN HASIL BELAJAR SISWA DENGAN MODEL BELAJAR KONSTRUKTIVISME PADA MATERI TANAH - Amiruddin, Amiruddin (CV Sintesia, 2025)
The purpose of this study was to determine the effect of implementing the constructivism learning model in order to improve student learning outcomes in class IXA SMPN 1 Anggaberi. The research was conducted at SMP Negeri 1 Anggaberi, Konawe Regency, class IX A with 22 students. The research was conducted in semester 2 (Even) of the 2020/2021 Academic Year from March to May 2021. The classroom action research design was planned to consist of two cycles. The first cycle of class IX A students carried out PBM activities with a constructivism learning model to explain soil structure, and the second cycle carried out PBM activities with a constructivism learning model to explain soil pollution. For research data collection as follows: (1) Observation, observation data collection is carried out when research actions in the teaching and learning process take place and (2) learning outcomes, for data collection learning outcomes and student absorption in participating in learning activities are taken from daily test instruments . The results of the research data analysis showed an increase in student learning outcomes classically by 80% with a predicate sufficient at the first meeting of cycle 1 activities and an increase in the second meeting with the percentage of classical learning outcomes reaching 84% with good predicates, and in the action activities cycle 2 also there is an increase in classical learning outcomes from 86% with good predicate to 93% with very good predicate at the second meeting.